1996
DOI: 10.1172/jci119013
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of inflammation-associated colonic injury in rat through inhibition of cyclooxygenase-2.

Abstract: Cyclooxygenase type 1 is constitutively expressed and accounts for synthesis of prostaglandins in the normal gastrointestinal tract. Cyclooxygenase-2 is expressed at sites of inflammation. Selective inhibitors of cyclooxygenase-2 have been suggested to spare gastrointestinal prostaglandin synthesis, and therefore lack the ulcerogenic effects associated with standard nonsteroidal antiinflammatory drugs. However, the effects of cyclooxygenase-2 inhibitors on inflamed gastrointestinal mucosa have not been examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
268
5
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(303 citation statements)
references
References 44 publications
24
268
5
6
Order By: Relevance
“…45 Another study using COX-2-specific inhibitors in rodents with a chemically induced colitis showed exacerbation with colonic perforation after 1 week of treatment. 46 This rodent model of colitis may not be representative of human UC, however, because it is induced by trinitrobenzene sulfonic acid and yields a different histological picture than typical UC, making direct comparisons tenuous.…”
Section: Cox-2 Selective Inhibitor Therapy In Sporadic and Uc Neoplasiamentioning
confidence: 99%
“…45 Another study using COX-2-specific inhibitors in rodents with a chemically induced colitis showed exacerbation with colonic perforation after 1 week of treatment. 46 This rodent model of colitis may not be representative of human UC, however, because it is induced by trinitrobenzene sulfonic acid and yields a different histological picture than typical UC, making direct comparisons tenuous.…”
Section: Cox-2 Selective Inhibitor Therapy In Sporadic and Uc Neoplasiamentioning
confidence: 99%
“…Previous studies have demonstrated the speci®city of these antibodies. 6 Tissues were viewed with an epi¯uoresence microscope (Axioplan; Carl Zeiss Inc., Thornwood, NY) and photographed using TMax 400 ASA black and white ®lm (Eastman Kodak Co., Rochester, NY).…”
Section: Cox Immunohistochemistrymentioning
confidence: 99%
“…11±13 However, it has been suggested that, in situations in which the mucosa is in¯amed, COX-2 is likely to be expressed and produce prostaglandins that contribute to mucosal defence and ulcer healing. 2,6,7 For example, in an animal model of colitis, administration of selective inhibitors of COX-2 resulted in exacerbation of tissue injury, 6 while in a mouse model of gastric ulcer, administration of a selective COX-2 inhibitor delayed healing. 7 Little is known of the regulation of COX-2 expression within the gastrointestinal tract following acute injury.…”
Section: Introductionmentioning
confidence: 99%
“…TNBS (100 mg/kg) in a vehicle of 50% ethanol (v/v) was instilled into the colon through the cannula. Following the instillation, the rats were held in a head-down position for 2 min to prevent the leakage of the intra-colonic instillation [26][27][28] . They were sacrificed 72 h after the colitis induction.…”
Section: Chemical Stimulation or Chemical Destruction Of Brain Nucleimentioning
confidence: 99%
“…The extent of macroscopic damage was assessed by a scoring system as described by Reuter et al [28] and Strober et al [29] with the following modifications: grade 0: no ulcer, no inflammation; grade 1: no ulcer, local hyperemia; grade 2: ulcer with no significant hyperemia and bowel wall thickening; grade 3: ulcer with one site of inflammation; grade 4: two or more sites of ulceration or inflammation; grade 5: major ulceration extending more than 1 cm along the length of the colon; grade 6-10: when the area of ulceration extended more than 2 cm along the colon, the score was increased by 1 for each additional cm of involvement. To assess the severity of diarrhea, the following criteria was used: grade 0: no diarrhea; grade 1: mild diarrhea; grade 2: severe diarrhea.…”
Section: Macroscopic Assessment Of Colonic Damage Score (Cds)mentioning
confidence: 99%